From Intended to Enacted: A Situated Analysis of TPACK-in-Action Through Video-Stimulated Recall in Geometry Classrooms - Umi Hanifah; Masriyah Masriyah; Ayu Silvi Lisvian Sari; Nurus Saadah; Jessica Dwi Nur Cahyani (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2026)
The integration of digital technology into mathematics classrooms remains inconsistent despite the development of the Technological Pedagogical Content Knowledge (TPACK) framework. This study investigates the persistent